The impact of forensic computing on telecommunications. - Patel, A.
The increasing use of telecommunications, particularly the development of e-commerce, is steadily increasing the opportunities for crime in many guises, especially IT-related crime. In response, there is an urgent new demand for forensic computing, that is, the examination of IT equipment and systems in order to obtain information for criminal or civil investigations. This field is not yet well developed, but its needs will in the future begin to influence telecommunications as investigations are extended to include the use of the communications infrastructures and services. IT security technologies alone are not sufficient to deal with this. The telecommunications industry, its customers, and regulators will face difficult challenges in the provision and use of systems that will be safe, reliable, and auditable. These challenges will need solutions addressing technical, legal, regulatory, and social issues and will not be easily resolved. This article summarizes the state of forensic computing, its likely future development, and its impact on telecommunications, and identifies several research and development issues.
Keywords: IT equipment; IT security technologies; IT systems; IT-related crime; Civil investigations; Communications infrastructures; Communications services; Criminal investigations; E-commerce.; Forensic computing; Legal issues; Regulatory issues; Research and development; Social issues; Telecommunications industry